Penatalaksanaan Fisioterapi pada Kasus Bell's Palsy Sinistra di RSU Aisyiyah Ponorogo - , Pujayanti (2015)
Background: Bell's Palsy is a facial nerve damage resulting in paralysis of the nerve, which causes abnormalities in the shape of the face (asymmetry). Knowing how big the problems that arise need to do examine for example for muscle strength by using Mmt facial muscles and the scale Ugo Fisch to evaluate the progress of patients with Bell's pasy motor. In addressing these problems modalities Infra Red, elektrical Stimulation and Massage can be obtained by an increase in muscle strength and increased motor facial muscles. Objective: To improve the knowledge and ability to learn, identify problems, analyze and take a conclusion about the condition of Bell's Palsy using the case study method with the implementation of the therapy six times. Results: After the treatment carried out during the six-times are as follows: an increase in visible increase in the value scale Ugo Fisch therapy for 6 times. T0 and T2 get the 24 points, then T3 increased to 36 points. At T4 value increase is 42 points. At T5 value increased to 58 points and the results of T6 increased again to 66 points. Mmt facial muscles on the frontal muscle, orbicularis oculi, Procerus, Corrugator Sepercilli, Nasalis, orbicularis Oris, zygomaticus major, Bucinator, mentalist value T0 muscle 1 (trace) T6 muscle value increased to 3 (fair). Oris Anguli depressor muscles niai T0-T6 niai 3 (fair). Methods: A case study in which patients studied and observed progress during therapy six times. Conclusion: Modality Physiotherapy Infrared (IR), Electrical Stimulation (ES) and Massage has been shown to increase muscle strength and functional facial face. Keywords: Bell's Palsy Infrared (IR), Electrical Stimulation (ES) and Massage